PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MICROSOFT POWER POINT PADA PEMBELAJARAN MATEMATIKA MATERI POKOK STATISTIK DI MTs Manhalul Ma’arif Darek Pada Tahun Ajaran 2020/2021 - Fadli, Saiful; Dasarja, Lalu Butsiawan (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2020)
This study aims to obtain the development of product results regarding the relationship between the use of Microsoft power point in mathematics learning. Related to student learning completeness in odd semester grades, it encourages researchers to want to improve student achievement and student motivation in mathematics. Therefore, researchers are encouraged to find out more about the Development of Microsoft Power Point-Based Interactive Learning Media in Mathematics Learning Subject Statistics at MTs Manhalul Ma'arif Darek. This type of research is research and development or Research and Development. The process of developing learning media based on Microsoft PowerPoint uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). While the implementation was carried out at MTs Manhalul Ma'arif Darek in class VIIIA. After the product has been validated by media and material experts, the next step is to distribute the student response questionnaires in small groups. After obtaining the percentage of student responses that meet the good category, it is continued with trying out learning media in-class activities. The product that will be produced in this research is a visual powerpoint presentation media with a contextual approach with Statistics material. The specialty of this developed media is power point which can run navigation buttons and slide shows